2010
DOI: 10.1105/tpc.109.073171
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate Provision to Plastids Is Essential for Gametophyte and Sporophyte Development inArabidopsis thaliana   

Abstract: Restriction of phosphoenolpyruvate (PEP) supply to plastids causes lethality of female and male gametophytes in Arabidopsis thaliana defective in both a phosphoenolpyruvate/phosphate translocator (PPT) of the inner envelope membrane and the plastid-localized enolase (ENO1) involved in glycolytic PEP provision. Homozygous double mutants of cue1 (defective in PPT1) and eno1 could not be obtained, and homozygous cue1 heterozygous eno1 mutants [cue1/eno1 (+/2)] exhibited retarded vegetative growth, disturbed flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 110 publications
(184 reference statements)
4
73
1
1
Order By: Relevance
“…The supply of this metabolite from the cytosol to the plastid is catalyzed by PPT (Knappe et al, 2003), which, at least in soybean seed, is present at the same site as lipid accumulates (Borisjuk et al, 2005). In Arabidopsis, the down-regulation of PPT depresses lipid accumulation (Prabhakar et al, 2010). Our work demonstrated that its up-regulation raised lipid accumulation by approximately 13%.…”
Section: Nmr Analysis Indicates a Trade Off Between Seed Size And Lipmentioning
confidence: 56%
“…The supply of this metabolite from the cytosol to the plastid is catalyzed by PPT (Knappe et al, 2003), which, at least in soybean seed, is present at the same site as lipid accumulates (Borisjuk et al, 2005). In Arabidopsis, the down-regulation of PPT depresses lipid accumulation (Prabhakar et al, 2010). Our work demonstrated that its up-regulation raised lipid accumulation by approximately 13%.…”
Section: Nmr Analysis Indicates a Trade Off Between Seed Size And Lipmentioning
confidence: 56%
“…In approximately 40% of the ovules, the embryo sac was diminished in size or even absent. 63 Besides the already mentioned plastidial enzymes, also mitochondrial proteins could be identified which are involved in pollen vitality and ovule or embryo development, respectively. For instance, GmAOX2b antisense plants exhibit increased rates of pollen abortion in vivo and reduced rates of pollen germination in vitro.…”
Section: Impaired Pollen Tube Growth Is Often Accompanied By Embryo Lmentioning
confidence: 99%
“…However, a heterozygous knock-out for eno1 in the homozygous cue1 (defective in PPT1) background (ccEe) possesses a reduced number of pollen containing a large portion of underdeveloped, non-vital, non-germinating pollen grains. 63 In addition, some of the mutant pollen accumulate a massive amount of starch in plastids indicating that starch degradation and subsequent glycolysis is inhibited. Therefore, no ATP can be generated via plastidial glycolysis to satisfy the high energy demand during pollen development and elongation.…”
Section: -56mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the presence of a complete glycolytic plastidial pathway in chloroplasts, specifically its lower part catalyzed by phosphoglycerate mutase and enolase, has even been questioned. [2][3][4] The reactions of plastidial/chloroplastic phosphoglycerate kinase (PGK) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) are particularly interesting because different isoforms of the same enzyme catalyze the same reactions, but in the opposite direction, of the plastidial glycolysis and Calvin cycle. Plastidial glycolytic GAPDH (GAPCp) converts glyceraldehyde-3-phosphate (GAP) into 1,3-bisphosphoglycerate (1,3-bisPGA), which is then converted into 3-phosphoglycerate (3-PGA) by plastidial PGK (PGKp).…”
Section: Gapcp Is Not Relevant In Photosynthetic Cellsmentioning
confidence: 99%